Italian validation of the credibility/expectancy questionnaire in spinal pain: a useful tool for clinicians and physiotherapist (CEQ-I) - Teresa Paolucci; Laura Belinda Rizzo; Giulia Patacchia; Chiara Sebastiani; Luca Furcas; Francesca Capuano; Marco Paoloni; Marta Di Nicola; Letizia Pezzi; Paola Borrelli (Therapeutic Advances in Chronic Disease)
Background: The “credibility” and “expectation” regarding the treatment are important factors in the rehabilitation management of patients with spinal pain (SP). Objectives: The aim of this study was to translate, culturally adapt, and validate an Italian version of the credibility/expectancy questionnaire (CEQ-I) by Devilly and Borkovec (CEQ) for its application in SP in rehabilitative care. Design: Cross-sectional observational study. Methods: Ninety-nine patients ( N = 99; mean age of 56.9 years ± 16.3 SD) with acute or chronic SP were recruited from September 2023 to September 2024. To evaluate construct validity, exploratory factor analysis (EFA) was conducted using a matrix of polychoric correlations along with promax rotation. The internal consistency and stability of the scale were evaluated using Cronbach’s alpha coefficient and test-retest analysis through the intraclass correlation coefficient (ICC). Pearson’s analysis between CEQ and other scales (Numeric Rating Scale, NRS; Roland and Morris-Disability Questionnaire, RMDQ; Oswestry Disability Index, ODI; Neuropathic Pain Symptom Inventory, NPSI) was employed to assess external validity. Results: Ninety-nine subjects were recruited. Test-retest reliability between two consecutive administrations of the CEQ showed an ICC of 0.90 ( p < 0.001). The Kaiser-Meyer-Olkin (KMO) statistic was 0.81, indicating suitability for factor analysis. EFA revealed two factors—credibility and expectancy—accounting for 56.6% of the variance. Cronbach’s alpha indicated high internal consistency (0.85). External validation using Pearson’s correlation found no significant relationships between the CEQ subscale scores and NRS, RMDQ, ODI, and NPSI scales. Conclusion: The CEQ-I is a valid Italian translation of CEQ that demonstrates acceptable psychometric properties in SP in a rehabilitative setting. However, we recommend further analysis of the construct definition of the CEQ-I.